The Influence of Media Literacy on Religious Moderation Among the Millennial Generation in Bulukumba Regency - Awal, Muhammad Syahdarul; Mau, Muliadi; Arianto (Dirasat: Human and Social Sciences, 2025)
Objectives: This research aims to analyze the influence of media literacy levels on religious moderation among millennial generations in Bulukumba Regency. This study classified as causal associative research based on the independent variable of media literacy (X) on the dependent variable of religious moderation (Y). Methods: The population and sample in the study were millennials who have participated in media literacy training and socialization of religious moderation. The technique is carried out using multi-stage cluster random sampling collected through questionnaires, interviews, and observations and used the Krejcie table. Data analysis used multivariate regression statistical analysis through SPSS version 26.0. Results: The research results: Partially, the influence of media literacy skills affects 44.9% of the attitude of religious moderation among millennial generations. Meanwhile, multivariately, each variable contributes different influence such as technical skills by 37.5%, critical skills by 19.9%, and communicative skills by 42.53%. Conclusions: Implications from the findings research were: 1) Reformulating and implementing communication strategies to enhance the attitude of religious moderation, following the principles of Appropriate Communication for the Development of Communities and participatory management based on the new communication and development paradigm; 2) Continuous media literacy socialization activities to be conducted by developing more systematic socialization strategies; 3) Reforming the communication process that considers the theory by (De Fleur, 1966) regarding the differences in communication effects, namely " the individual differences theory" and "the social category theory."